Household Economic of Shallot Farmers in Central Java Province, Indonesia - Fauzan, Muhammad (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to comprehensively analyze the economic comparison of shallot farmers' households, seen through income and profits. This includes analyzing the shallot agribusiness system and its development strategy in Central Java Province. Data collection was conducted on 140 respondents in the Brebes, Demak, and Pati Regencies. Income and profits were calculated and compared between locations using parametric tests, regression analysis, and measurement of inequality. The results showed that Brebes Regency's average shallot farming income was still relatively high, at IDR 51,338,602,-/farm or IDR 51,225,994,-/ha, higher than in Demak and Pati regencies. The life cycle of farmers, both productive and unproductive/old age groups, has no significant effect on the income and profits of shallot farming. Other factors, such as experience and the number of family members of farmers, affect income and profits.